2019
DOI: 10.4038/seajme.v13i1.61
|View full text |Cite
|
Sign up to set email alerts
|

Use of Flipped model classroom teaching on learning of Immunology in second professional medical students

Abstract: Objectives: Over time medical para-clinical subject teachers have felt that undergraduate students have difficulty in understanding immunological concepts of infections. The objectives of the study were to compare the effectiveness of traditional method of teaching with the flipped classroom teaching (FCT) model in Immunology and to assess the perception of students towards the flipped classroom teaching (FCT) model using semi-structured feedback.Methodology: In the study, the flipped classroom model was emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Their overall scores were also significantly higher in post-test assessment. 16 One of the key points in any educational process is students' satisfaction and acceptance of educational methods. Strayer et al, performed a comparative study between a flipped classroom and the traditional classroom and demonstrated that students participating in the flipped classroom were less satisfied.…”
Section: Discussionmentioning
confidence: 99%
“…Their overall scores were also significantly higher in post-test assessment. 16 One of the key points in any educational process is students' satisfaction and acceptance of educational methods. Strayer et al, performed a comparative study between a flipped classroom and the traditional classroom and demonstrated that students participating in the flipped classroom were less satisfied.…”
Section: Discussionmentioning
confidence: 99%
“…Ketika guru senantiasa memberikan umpan balik secara positif, maka siswa akan melakukan upayaupaya untuk memperbaiki kesalahan meraka. Hasil ini sejalan dengan temuan penelitian sebelumnya yang dilakukan oleh (Gupta, et al 2019;Ginola & Magdalena 2016). Mereka menyatakan bahwa siswa-siswa sepakat flipped learning model memberikan pengalaman belajar yang inovatif dalam meningkatakan keterampilan berbicara berbahasa Inggris mereka.…”
Section: Metodologi Penelitianunclassified
“…health care (HLC) and general BMDW processing facility operator. In the interest of the general public, the 2016 Regulations for BMDW Management, as revised on the 28 March 2018, is further amended (Gupta et al, 2019;Chavan, 2020;George and Gupta, 2020;Mohan et al, 2020;Yadav et al, 2020).…”
Section: Introductionmentioning
confidence: 99%